Encuesta sobre Derecho de gracia, amnistía y Constitución - Aguado Renedo, César; Carmona Contreras, Ana; Gil Gil, Alicia; Linde Paniagua, Enrique; López Basaguren, Alberto; Saiz Arnaiz, Alejandro (Teoría y Realidad Constitucional, 2024)
Encuesta sobre Derecho de gracia, amnistía y Constitución